2017
DOI: 10.1249/mss.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Time among Children with Disabilities at School

Abstract: This is the first study to examine MVPA and ST among different disability types at school using accelerometry. Given the low levels of PA, this population should receive priority in the development of cost-effective interventions to improve their PA opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 24 publications
3
55
3
Order By: Relevance
“…In addition, all children in this study were at school during physical activities assessment, and this could be the reason why all children spent most of their time in sedentary activities, with the percentages of total sedentary time between 60.18 ± 10.62 and 67.93 ± 6.96. These results were consistent with a study done by Sit et al [34], which reported that children spent more than 70% of their overall time at school being sedentary.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, all children in this study were at school during physical activities assessment, and this could be the reason why all children spent most of their time in sedentary activities, with the percentages of total sedentary time between 60.18 ± 10.62 and 67.93 ± 6.96. These results were consistent with a study done by Sit et al [34], which reported that children spent more than 70% of their overall time at school being sedentary.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, whether a longer intervention program is able to reveal a positive body composition change among students with physical disability is still considered as uncertain ( Table 2). 4 Asian J Sports Med. 2020; 11(1):e98225.…”
Section: Body Compositionmentioning
confidence: 99%
“…ities reported that only 26% of the physically disabled children in special education school did participate in sports regularly compared to over 70% in non-disabled youth (14). Therefore, the low level of physical activity engagement and fitness of children with disabilities were associated with inferior health status, in both physical and mental health (4,15). It can be known that there were various factors leading to the lack of physical activity and poor fitness of children and adolescents with disabilities; for instance, lack of assistance from caregivers, lack of physical activity (PA) opportunities, concern for the children's safety, lack of professional teacher training, insufficient facilities at school for disabilities or other socio-environmental factors (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations